2012
DOI: 10.1134/s1022795412050171
|View full text |Cite
|
Sign up to set email alerts
|

Increase in NETO2 gene expression is a potential molecular genetic marker in renal and lung cancers

Abstract: Multiple changes in the genome, transcriptome, and proteome are frequent in cancer cells. A search for molecular markers based on DNA, mRNA, or proteins is a main method to develop early specific diagnostics for cancer. While universal markers are still unavailable, similar trends are known for the expres sion patterns of particular genes in certain epithelial tumors. A bioinformatic screening of transcriptomic databases identified the NETO2 gene as a new potential promising marker of renal cancer. A substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Using real-time qPCR and Western blot analysis, we found that NETO2 was frequently overexpressed in primary CRC samples at both the mRNA and protein levels. Our results are consistent with the previous findings of Oparina et al at the mRNA level [ 16 ]. Of note, we observed a significant increase in NETO2 mRNA level (over 2-fold) in 52.6 % (30/57) of the cancerous specimens tested, whereas Oparina et al reported that only 40 % (4/10) of colon cancer samples showed substantially increased expression of NETO2 mRNA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Using real-time qPCR and Western blot analysis, we found that NETO2 was frequently overexpressed in primary CRC samples at both the mRNA and protein levels. Our results are consistent with the previous findings of Oparina et al at the mRNA level [ 16 ]. Of note, we observed a significant increase in NETO2 mRNA level (over 2-fold) in 52.6 % (30/57) of the cancerous specimens tested, whereas Oparina et al reported that only 40 % (4/10) of colon cancer samples showed substantially increased expression of NETO2 mRNA.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, Horak et al found that it could be downregulated by the metastasis suppressor gene Nm23-H1 in breast carcinoma cell lines [ 23 ]. Notably, Oparina et al recently demonstrated that the NETO2 mRNA is frequently overexpressed in a number of human neoplasms and might be a tool to support the early diagnosis of renal and lung carcinomas [ 16 ]. These findings indicate that NETO2 may have potential significance in cancer pathobiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4D), involving two overlapping inversions (62 and 125 kb) and a tandem duplication (163 kb). These events affect ORC6, MYLK3, RHBDF1 (previously known as C16orf8), and NETO2, which has recently been identified as a cancer marker gene (Oparina et al 2012;Hu et al 2015). This rearrangement resides on the nonduplicated haplotype of this triploid region.…”
Section: Identification and Reconstruction Of Structural Variants (Svmentioning
confidence: 99%
“…Numerous genetic and epigenetic changes, occurring in ccRCC, effect transcription of many genes and lead to alterations in different metabolic pathways. [3][4][5][6][7][8] Deregulation of metabolic pathways in ccRCC determines its aggressive phenotype. [9] Understanding the molecular mechanisms leading to altered metabolic pathways in ccRCC could provide novel targets for therapies and diagnostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%